Fluorine-silicon-containing polymer with multi-layer core-shell structure, and preparation method and application of resin composition comprising fluorine-silicon-containing polymer with multi-layer core-shell structure

By using a multi-layer core-shell structure polymer with fluorine silicone in ABS resin and combining reaction technology of vinyl siloxane, fluorine silicone and alkyl siloxane, the hydrophobicity and resistance of existing ABS resins are solved by using fluorine silicone in ABS resin. The problem of insufficient chemical properties has achieved significant improvement in the performance of the resin composition.

CN119463061APending Publication Date: 2025-02-18KINGFA SCI & TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411592303.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ABS resins have insufficient performance in improving hydrophobicity and chemical resistance, especially when adding fluorosiloxane modifiers, which leads to poor dispersion and chemical resistance of the overall resin.

Method used

Using a multi-layer core-shell structure polymer with fluorine silicone, a shell layer is formed by reaction of vinyl siloxane, fluorine silicone and alkyl siloxane, and combined with the core and intermediate layer by emulsion polymerization technology. , a resin composition having excellent hydrophobicity and chemical resistance is formed.

Benefits of technology

The hydrophobicity and chemical resistance of the resin composition are significantly improved, so that it has higher performance requirements in applications in automobiles, home appliances and other fields, such as better self-cleaning ability and chemical solvent resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125905980000031
    Figure BDA0005125905980000031
  • Figure BDA0005125905980000091
    Figure BDA0005125905980000091
  • Figure BDA0005125905980000101
    Figure BDA0005125905980000101
Patent Text Reader

Abstract

The invention discloses a fluorine-silicon-containing multi-layer core-shell structure polymer, and a preparation method and application of a resin composition containing the polymer, and belongs to the field of high polymer materials. The fluorine-silicon-containing multi-layer core-shell structure polymer comprises an inner core, an outer shell layer and an optional middle shell layer. The shell layer is obtained through reaction of vinyl siloxane, fluorine-containing siloxane and alkyl siloxane, and is bridged on the inner core or the middle layer through the vinyl siloxane. The prepared multi-layer core-shell polymer with the fluorine-containing polysiloxane as the shell layer is beneficial to subsequent improvement of hydrophobicity and chemical resistance of a resin composition comprising the multi-layer core-shell polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a fluorine-silicon-containing multilayer core-shell structure polymer, and a preparation method and application of a resin composition comprising the same. Background Art

[0002] After the impact modifier of polybutadiene rubber grafted SAN is blended with SAN, ABS resin with a classic island structure can be obtained, which has good rigidity, processing performance and impact resistance, and is widely used in the fields of automobiles and home appliances. With the advancement of polymer synthesis technology, people's demand for the special properties of ABS materials continues to increase. For example, automobile and home appliance parts need to have good hydrophobicity and chemical resistance; they can have a certain self-cleaning ability to prevent sweat and stains from penetrating into the material. The improvement of chemical resistance can keep the dimensional stability of the material during the chemical solvent treatment of electroplating and finishing paint to avoid cracking and cracking of the product.

[0003] In the prior art, the methods for improving the hydrophobicity and chemical resistance of ABS resin mainly focus on the modification and reinforcement of the sea phase structure, while the high-rubber powder (island phase structure) usually becomes the low point of performance improvement. Directly adding fluorinated silicone to the extruded ABS resin for modification has poor dispersibility, and usually the overall resin hydrophobicity and chemical resistance are still poor due to the performance defects of the high-rubber powder. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems or defects existing in the above-mentioned prior art and provide a fluorine-silicon-containing multilayer core-shell structure polymer and a resin composition comprising the same. The obtained resin composition has good hydrophobicity and chemical resistance.

[0005] Another object of the present invention is to provide a method for preparing the fluorine-silicon-containing multi-layer core-shell structure polymer.

[0006] Another object of the present invention is to provide a resin composition comprising the multi-layer core-shell structure polymer containing fluorine and silicon.

[0007] Another object of the present invention is to provide a method for preparing the resin composition comprising the fluorine-silicon-containing multi-layer core-shell structure polymer.

[0008] Another object of the present invention is to provide an application of the resin composition comprising the multi-layer core-shell structure polymer containing fluorine and silicon.

[0009] To achieve the above object, the present invention is implemented by the following technical solutions:

[0010] A multilayer core-shell structure polymer containing fluorine and silicon, wherein the outer shell layer comprises the following components based on 100 parts by dry basis weight of the inner core and the middle layer:

[0011] 5-25 parts of fluorinated silicone;

[0012] 5-15 parts of vinyl siloxane;

[0013] Alkyl siloxane 0-20 parts;

[0014] The number of the intermediate layers is n, where n is a positive integer of 0 to 10; and the core includes a diene polymer.

[0015] In the above scheme, a multilayer core-shell structure polymer containing fluorine silicon is provided, and the multilayer core-shell structure polymer containing fluorine silicon comprises a core, an outer shell layer and an optional intermediate shell layer. The outer shell layer is obtained by reacting vinyl siloxane, fluorine-containing siloxane and alkyl siloxane, and is bridged to the core or the intermediate layer by vinyl siloxane. The prepared multilayer core-shell polymer with fluorine-containing polysiloxane as the outer shell layer helps to improve the hydrophobicity and chemical resistance of the resin composition containing the same in the subsequent step.

[0016] Further, n is 0-5; further, n is 1-3.

[0017] Furthermore, the core includes polyconjugated diene and / or inorganic particles coated with polyconjugated diene.

[0018] Specifically, the polyconjugated diene is obtained by polymerizing conjugated diene monomers.

[0019] The average particle size of the core is 290-330 nm, the solid content of the core is 40%-60%, the gel content of the core is 60-95%, and the core is usually dispersed in water in the form of emulsion.

[0020] Specifically, the average particle size was determined by diluting the sample in water and then adding the sample to the sample pool of the Malvern laser particle size analyzer. Each sample was scanned and measured three times, the measurement balance time was set to 10 seconds, and the single scan time was 60 seconds.

[0021] Specifically, the conjugated diene monomer is at least one selected from 1,3-butadiene, isoprene, 2-chloro-1,3-butadiene and chloroprene.

[0022] The polyconjugated diene in the present invention can be commercially available or homemade.

[0023] Specifically, the polyconjugated diene is prepared by the following method:

[0024] Obtained by emulsion polymerization of conjugated diene monomers.

[0025] Specifically, the temperature of the emulsion polymerization is 60 to 90° C., and the time of the emulsion polymerization is 12 to 36 hours.

[0026] Specifically, one or more of an initiator, an emulsifier, a defoamer, a chain transfer agent or an electrolyte may be added to the emulsion polymerization.

[0027] In some specific embodiments, the core is an inorganic particle coated with a polyconjugated diene, and the preparation method is as follows:

[0028] Obtained by emulsion polymerization of conjugated diene monomers in the presence of inorganic particles; or

[0029] It is obtained by emulsifying polyconjugated diene latex and inorganic particles.

[0030] Specifically, the inorganic particles are one or more of inorganic silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, titanium dioxide or rare earth oxides; the inorganic particles may be surface-modified particles or non-surface-modified particles.

[0031] The surface modification includes silane modification.

[0032] The inorganic particles can be purchased from the market or prepared by themselves. The preparation method includes the sol-gel method.

[0033] In a specific embodiment, the inorganic silica is nano-silica modified by vinyltriethoxysilane.

[0034] Furthermore, the intermediate layer is obtained by emulsion polymerization of components including the following compounds:

[0035] A11: based on the intermediate layer, 40 to 79.9 wt% of at least one vinyl aromatic olefin; preferably 45 to 70 wt% of at least one vinyl aromatic olefin; preferably 48 to 60 wt%; more preferably 50 to 65 wt%;

[0036] A12: Based on the middle layer, 10 to 39.9 wt% of acrylonitrile monomer; preferably 15 to 30 wt% of acrylonitrile monomer; preferably 22 to 28 wt%; more preferably 24 to 26 wt%;

[0037] A13: based on the intermediate layer, 10 to 29.9 wt% of the divinyl compound; preferably 15 to 28 wt% of the divinyl compound; preferably 18 to 27 wt%; more preferably 20 to 25 wt%;

[0038] The mass ratio of the middle layer to the inner core is 20:80 to 80:20 on a dry basis.

[0039] Further, the divinyl compound has the following structural formula:

[0040]

[0041] wherein R1 is selected from substituted or unsubstituted alkylene, cycloalkylene, alkylene ester, cycloalkylene ester, alkyleneoxy, cycloalkyleneoxy, arylene, arylalkylene, and heteroarylene; and the number of carbon atoms in R1 is 1 to 20;

[0042] R2 and R3 are independently selected from hydrogen, alkyl, cycloalkyl, alkylcarboxyl, cycloalkylcarboxyl, alkoxy, cycloalkyloxy, aryl, aralkyl, and heteroaryl groups having 1 to 20 carbon atoms.

[0043] Furthermore, the divinyl compound is one or more of divinylbenzene, polyethylene glycol dimethacrylate (n=1-60), polyethylene glycol diacrylate (n=1-60), propylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,4-butylene glycol dimethacrylate, aryl methacrylate, diethylene glycol dimethacrylate, trimethylolpropane triacrylate, polybisphenol A-ethylene oxide diacrylate (n=1-40), tetraethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethylene glycol dimethacrylate or divinyl ether.

[0044] Furthermore, the divinyl compound is one or more of divinylbenzene, ethylene glycol dimethacrylate or divinyl ether.

[0045] Furthermore, the divinyl compound is divinylbenzene.

[0046] Furthermore, the fluorine-containing siloxane includes one or more of trifluoropropylmethylcyclotrisiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane or 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane.

[0047] Furthermore, the fluorine-containing siloxane is trifluoropropylmethylcyclotrisiloxane and / or tetramethyltri-3-trifluoropropylcyclotetrasiloxane.

[0048] Furthermore, the vinyl siloxane includes one or more of tetramethyltetravinylcyclotetrasiloxane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane or vinyltriisopropoxysilane.

[0049] Furthermore, the vinyl siloxane is tetramethyltetravinylcyclotetrasiloxane and / or γ-methacryloxypropyltrimethoxysilane.

[0050] Furthermore, the alkylsiloxane includes one or more of octamethylcyclotetrasiloxane, hexamethyldisiloxane, hexaethyldisiloxane, methyltriethoxysilane or 1,3-octyltetramethyldisiloxane.

[0051] Furthermore, the alkylsiloxane is one or more of octamethylcyclotetrasiloxane, hexamethyldisiloxane or hexaethyldisiloxane.

[0052] Furthermore, the outer shell layer comprises the following components:

[0053] 17.5 to 22.5 parts of fluorine-containing silicone.

[0054] 8-15 parts of vinyl siloxane.

[0055] 8-15 parts of alkyl siloxane.

[0056] Furthermore, the preparation method of the fluorine-silicon-containing multilayer core-shell structure polymer comprises the following steps:

[0057] S1. Prepare or prepare the kernel;

[0058] S2. Preparation of core-shell emulsion: A11, A12 and A13 were emulsion polymerized in the presence of the core;

[0059] S3. polymerizing the product obtained in step S2, fluorinated siloxane, alkyl siloxane and vinyl siloxane to obtain a polymer emulsion, and condensing the polymer emulsion at high temperature to obtain a fluorinated silicon-containing multilayer core-shell structure polymer.

[0060] Specifically, the temperature of the emulsion polymerization is 60 to 90° C., and the time of the emulsion polymerization is 2 to 6 hours.

[0061] Specifically, the emulsion polymerization may add 0.1 to 10 parts by weight of other component C1 based on 100 parts by dry basis of the core.

[0062] Specifically, the polymerization reaction temperature is 60 to 90° C., and the polymerization reaction time is 2 to 6 hours.

[0063] Specifically, the temperature of the high temperature condensation is 80-100°C.

[0064] Specifically, the other component C1 can be selected from one or more of a redox initiator, a reducing agent, a reducing aid, a lubricant, a chain transfer agent or a defoaming agent.

[0065] Specifically, 0.1 to 10 parts by weight of other component C2 based on 100 parts by weight of the product of step S2 on a dry basis may be added to the polymerization reaction.

[0066] Specifically, the other component C2 can be selected from an initiator and / or an emulsifier. Preferably, the initiator is a redox initiator.

[0067] Specifically, based on 100 parts of the dry product of step S2, 0.1 to 5 parts by weight of initiator, 0.1 to 5 parts by weight of emulsifier; and 60 to 350 parts by weight of water.

[0068] In a specific embodiment, the fluorine-silicon-containing multilayer core-shell structure polymer is prepared by the following method:

[0069] S1. Prepare or prepare the kernel;

[0070] S2. The core, part of the vinyl aromatic olefin and acrylonitrile monomer, based on 100 parts of dry core, 0.3 to 0.8 parts by weight of reducing agent, 1.5 to 2.5 parts by weight of auxiliary reducing agent, 0.3 to 0.8 parts by weight of emulsifier and 80 to 200 parts by weight of water are added to the reactor, the temperature is raised to 65 ± 3 ° C, 1 part by weight of initiator is added to react for 0.5 to 1.5 hours, the temperature is raised to 78 ± 3 ° C, the remaining vinyl aromatic olefin, the remaining acrylonitrile monomer and divinyl compound and 1 part by weight of initiator are continuously added dropwise, and the reaction time is 1.0 to 5.0 hours;

[0071] S3. The product of step S2 (solid content of 40-65%), fluorinated silicone, vinyl silicone and alkyl silicone are added to a reactor based on 100 parts of dry basis step S2, 0.8-2 parts by weight of initiator, 0.8-2 parts by weight of emulsifier and 80-200 parts by weight of water, and reacted at 65-75° C. for 2.5-3.5 hours to obtain a multilayer core-shell polymer emulsion with a solid content of 40-65%, which is then transferred to a coagulation reactor and heated to 8 0-90°C, gradually add sulfuric acid with a mass concentration of 3-8% (the amount added is 30%-50% of the multi-layer core-shell structure polymer emulsion), add it over 2.5-3.5 hours, and raise the temperature to 90-99°C and maintain the temperature for 2-4 hours, filter the obtained coagulated latex with a filter (for example, filter with a 200-500 mesh filter), and dry it with a fluidized bed dryer at 65-75°C for 5-8 hours to obtain a fluorine-silicon-containing multi-layer core-shell structure polymer with a water content of less than 1%.

[0072] Furthermore, the vinyl aromatic olefin includes one or more of styrene, p-methylstyrene and α-methylstyrene.

[0073] In the present invention, commonly used redox initiators may be selected, such as but not limited to one or more of hydrogen peroxide, dibenzoyl peroxide or cyclohexylbenzene hydroperoxide.

[0074] In the present invention, commonly used reducing agents may be selected, such as but not limited to ferrous sulfate and / or ferric sulfate.

[0075] In the present invention, commonly used reducing agents may be selected, such as but not limited to one or more of lactose, glucose, maltose, and formaldehyde sulfoxylate.

[0076] In the present invention, commonly used emulsifiers may be selected, such as but not limited to one or more of potassium disproportionate rosin acid, potassium fatty acid, or dodecylbenzene sulfonic acid.

[0077] In the present invention, commonly used chain transfer agents may be selected, such as but not limited to n-dodecyl mercaptan and / or tert-dodecyl mercaptan.

[0078] In the present invention, commonly used electrolytes may be selected, such as but not limited to one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate or potassium hydroxide.

[0079] In the present invention, commonly used defoamers may be selected, such as but not limited to polyether defoamers, silicone defoamers or non-silicon defoamers.

[0080] The present invention also provides a polymer composition, which comprises the following components calculated in parts by weight:

[0081] 15-40 parts of the above-mentioned fluorine-containing silicon multilayer core-shell structure polymer or the fluorine-containing silicon multilayer core-shell structure polymer prepared by the above-mentioned preparation method; 60-80 parts of styrene-acrylonitrile copolymer and / or styrene-acrylonitrile-acrylate copolymer.

[0082] Specifically, the styrene content in the styrene-acrylonitrile copolymer and the styrene-acrylonitrile-acrylate copolymer is 60-80wt%.

[0083] In a specific embodiment, the polymer composition further comprises 0.1 to 5 parts by weight of other components.

[0084] In a specific embodiment, the other components include, but are not limited to, one or more of fillers, reinforcing agents, dyes, lubricants, release agents, stabilizers, antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides or foaming agents.

[0085] Specifically, the filler or reinforcing agent includes, but is not limited to, one or more of silicate, amorphous silicon dioxide, calcium silicate, quartz, mica, metal oxide, metal hydroxide, graphite, barium sulfate, calcium carbonate, magnesium carbonate, talc, kaolin, carbon fiber or glass fiber.

[0086] Specifically, the pigment includes but is not limited to one or more of titanium dioxide, phthalocyanine, ultramarine, iron oxide or carbon black.

[0087] Specifically, the stabilizer includes but is not limited to one or more of benzophenone, salicylate, benzotriazole or benzophenone.

[0088] Specifically, the release agent includes, but is not limited to, fatty acids having 12 to 30 carbon atoms, salts thereof, and derivatives thereof, such as stearic acid, stearate, palmitic acid, palmitate, stearyl alcohol, amide wax, polyolefin wax, and the like.

[0089] In the present invention, commonly used antioxidants may be selected, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.

[0090] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate n-octadecyl or spiroethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].

[0091] Specifically, the phosphite antioxidant is 2,4-di-tert-butylphenol and / or bis(2,6-di-tert-butyl-4-tolyl)pentaerythritol phosphite.

[0092] Specifically, the thioester antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.

[0093] In the present invention, commonly used lubricants may be selected, such as but not limited to at least one of amide lubricants, stearate lubricants, ester lubricants or silicone lubricants.

[0094] The present invention also provides a method for preparing the polymer composition, comprising the following steps:

[0095] The components are mixed, extruded through a twin-screw extruder, cooled, and granulated to obtain a polymer composition.

[0096] Specifically, the extrusion temperature is 185-220°C.

[0097] Specifically, the screw speed of the twin-screw extruder is 250-350 rpm.

[0098] Specifically, the screw length-to-diameter ratio of the twin-screw extruder is 25:1.

[0099] The present invention also provides the use of the polymer composition in the preparation of materials such as automobiles, household appliances and office equipment, especially in automobile door handles, automobile interiors, automobile steering wheels, juicers, coffee machines or printers.

[0100] Compared with the prior art, the present invention has the following beneficial effects:

[0101] The invention provides a fluorine-silicon-containing multilayer core-shell structure polymer, wherein the outer shell layer is composed of fluorine-containing silicone and vinyl silicone, and the polymer composition prepared by using the fluorine-containing silicone has good hydrophobicity and chemical resistance. DETAILED DESCRIPTION

[0102] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0103] 1. Raw materials used in each embodiment and comparative example:

[0104] Core 1: polybutadiene latex: homemade, average particle size 325.1nm, solid content 45.8%;

[0105] The specific preparation method is as follows:

[0106] 1 part by weight of sodium hydroxide, 1.5 parts by weight of potassium disproportionate rosin acid, 0.5 parts by weight of tert-dodecyl mercaptan and 130 parts by weight of water are added into a high-pressure reactor, and then 90 parts by weight of butadiene monomer and 1 part by weight of potassium persulfate are pressed into the reactor via medium-pressure nitrogen. The temperature is raised to 60°C for reaction for 18 hours, and finally the temperature is raised to 80°C for reaction for 10 hours to obtain polybutadiene latex.

[0107] Core 2: polybutadiene-coated inorganic silica: homemade, average particle size 329.1nm, solid content 50.2%;

[0108] 50 parts by weight of water, 20 parts by weight of methanol, 5.0 parts by weight of sodium hydroxide, 10 parts by weight of nano-silicon dioxide with an average particle size of 30 nm, and 5.0 parts by weight of vinyltriethoxysilane are added into a high-pressure reactor, stirring is started, and the reactor is heated to 80° C. and kept warm for 20 minutes; the temperature is lowered to 60° C., 1 part by weight of sodium hydroxide, 1.5 parts by weight of potassium disproportionate rosin acid, 0.5 parts by weight of tert-dodecyl mercaptan and 130 parts by weight of water are added into the high-pressure reactor, and then 90 parts by weight of butadiene monomer and 1 part by weight of potassium persulfate are pressed into the reactor via medium-pressure nitrogen, the temperature is raised to 60° C. for reaction for 18 hours, and finally the temperature is raised to 80° C. for reaction for 10 hours to obtain polybutadiene latex coated with inorganic silica.

[0109] Specifically, the average particle size test method is: disperse the sample in water and dilute it, then add the sample to the sample cell of the Malvern laser particle size analyzer. Each sample is scanned and measured three times to take the average value, the measurement balance time is set to 10s, and the single scan time is 60s.

[0110] Specifically, the solid content test method is as follows: first weigh the mass W1 of the aluminum foil used for sampling; after sampling, in order to avoid the volatilization of the monomer, the total mass W2 of the aluminum foil and latex should be weighed immediately; put the aluminum foil and latex into a blast oven, dry them at 110°C to constant weight, and weigh the weight after drying W3. The solid content calculation method is: solid content = (W3-W 1) / (W2-W1)×100%, where

[0111] W1: mass of aluminum foil, g;

[0112] W2: mass of aluminum foil and latex, g;

[0113] W3: mass of aluminum foil and dry glue, g;

[0114] A11: vinyl aromatic olefin, industrial grade styrene, purity greater than 99.5%, purchased from Inokai;

[0115] A12: acrylonitrile monomer, industrial grade acrylonitrile, purity greater than 99%, purchased from Inokai;

[0116] A13: Divinyl compounds

[0117] A13-1: divinylbenzene, purity greater than 98%, purchased from Inokai;

[0118] A13-2: Ethylene glycol dimethacrylate, purity greater than 98.5%, purchased from Sinopharm Reagent;

[0119] A13-3: divinyl ether, purity greater than 98%, purchased from Inokai;

[0120] Fluorosilicone:

[0121] Fluorosiloxane 1: trifluoropropylmethylcyclotrisiloxane, purity greater than 98%, purchased from Inokai;

[0122] Fluorosiloxane 2: tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, purity greater than 96%, purchased from Inokai;

[0123] Vinyl Siloxane:

[0124] Vinyl siloxane 1: γ-methacryloxypropyltrimethoxysilane, purity greater than 98%, purchased from McLean;

[0125] Vinylsiloxane 2: tetramethyltetravinylcyclotetrasiloxane, purity greater than 97%, purchased from J&K;

[0126] Alkyl siloxane: octamethylcyclotetrasiloxane; purchased from Aladdin;

[0127] Nano-silicon dioxide, 20-30 nm, purchased from Inokai, purity greater than 99%, powder, product number A66412;

[0128] Vinyl triethoxysilane, purity greater than 98%, purchased from Inokai;

[0129] Initiator: potassium persulfate, commercially available;

[0130] Initiator: dibenzoyl peroxide, commercially available;

[0131] Electrolyte: sodium carbonate, commercially available;

[0132] Emulsifier: potassium disproportionate rosin acid, commercially available;

[0133] Chain transfer agent: tert-dodecyl mercaptan, commercially available;

[0134] Reducing agent: ferrous sulfate, commercially available;

[0135] Reducing agent: sodium formaldehyde sulfoxylate, commercially available;

[0136] Styrene-acrylonitrile copolymer: KFA-130, styrene content 76wt%, purchased from Liaoning Kingfa Technology;

[0137] Other components C3:

[0138] Antioxidant: phosphite antioxidant, commercially available;

[0139] Lubricant: a commercially available mixture of ethylene bisstearamide and magnesium stearate in a mass ratio of 1:1; it should be noted that the raw materials used in the parallel experiments of the embodiment and the comparative example are the same commercially available products.

[0140] Examples 1 to 12 and Comparative Examples 1 to 2

[0141] In the examples and comparative examples, the fluorine-silicon-containing multilayer core-shell structure polymer is prepared by the following method, including the following steps, with the raw material ratios shown in Tables 1 to 2 in parts by weight:

[0142] S1. According to the formula in Table 1, the kernel (emulsion, the amount is calculated according to the dry weight), part of styrene and acrylonitrile monomers (50wt% each), based on 100 parts of the dry kernel, 0.5 parts by weight of ferrous sulfate, 2 parts by weight of sodium formaldehyde sulfoxylate, 1.5 parts by weight of potassium disproportionate rosin acid and 100 parts by weight of water are added to the reactor, the system is heated to 65°C, 1 part by weight of dibenzoyl peroxide is added and reacted for 1h, the temperature is raised to 78°C, the remaining styrene, acrylonitrile monomer and divinyl compound and 1 part by weight of dibenzoyl peroxide are continuously added dropwise, and the reaction time of the addition at 78°C is maintained for 4h to obtain a core-shell structure emulsion (solid content of 48.4%) (specific amounts of each component are shown in Table 1);

[0143] S2. According to the formula in Table 2, the product of step S1 (emulsion, the amount is calculated on a dry basis), fluorinated silicone, vinyl silicone, alkyl silicone, 1% potassium persulfate based on the dry basis weight of the product of step S1, 1% potassium disproportionate rosin acid and 100% water are added to a reactor, the system is heated to 70°C and reacted for 3 hours to obtain a multilayer core-shell polymer emulsion with a solid content of 42.5%, 1500 parts by weight of the product are transferred to a coagulation reactor while maintaining the temperature, heated to 85°C, 550 parts by weight of 5% sulfuric acid are gradually added over a period of 3 hours, and the temperature is raised to 95°C and maintained for 3 hours. The resulting coagulation latex is filtered using a 325-mesh filter and dried at 70°C for 6 hours using a fluidized bed dryer to obtain a multilayer core-shell polymer with a moisture content of less than 1%.

[0144] Table 1 Selection and dosage of raw materials for the core and the middle layer in step S1 of the embodiments and comparative examples. (Unit: parts by weight)

[0145]

[0146]

[0147] Note: A11, A12 and A13 are all based on the middle layer. The middle layer is obtained by emulsion polymerization of A11, A12 and A13, and the sum of the percentages of the three is 100%.

[0148] Table 2 Selection and dosage of each raw material in step S2 in the embodiments and comparative examples (unit: weight parts)

[0149]

[0150] Examples 13 to 24 and Comparative Examples 3 to 4

[0151] In Examples 13 to 24 and Comparative Examples 3 to 4, the polymer composition is prepared according to the formulation in Table 3 by the following method, which comprises the following steps:

[0152] The fluorine-silicon-containing multilayer core-shell structure polymer, styrene-acrylonitrile copolymer, antioxidant and lubricant are uniformly mixed, extruded by a twin-screw extruder, cooled and granulated to obtain a polymer composition; the extrusion temperature is 185-220°C, the screw speed is 300rpm, and the screw aspect ratio is 25:1.

[0153] Table 3 Formulation of polymer composition in Examples 13 to 24 (unit: parts by weight)

[0154]

[0155]

[0156] Performance Testing

[0157] The polymer compositions prepared in the above examples and comparative examples were subjected to performance tests, and the specific test items and test methods are as follows:

[0158] 1. Test method:

[0159] (1) Notched impact performance test: The polymer compositions described in the above embodiments and comparative examples were tested for their simple supported beam impact strength according to ISO 179 (1993).

[0160] (2) Contact angle test: The experiment uses a contact angle meter (OCA20, Data physics, Germany) to characterize the hydrophobicity of the polymer composition. The operation is as follows: At room temperature, 1 microliter of water droplets are quickly dropped onto the surface of a 10 cm*10 cm square plate molded with plastic particles. The camera continuously captures images of the droplets on the film surface, determines the droplet profile and baseline, and selects an appropriate method to fit the droplet profile curve to obtain the static contact angle of the square plate surface. In order to reduce experimental errors, 5 points are randomly selected on the sample surface for measurement, and the average value is recorded and calculated as the final result. The contact angle ≥85° is considered to have good self-cleaning ability.

[0161] (3) Determination of cracking time: The polymer compositions described in the above examples and comparative examples were prepared into 60*10*2 mm specimens, placed in a mixed solution of ethyl acetate / ethanol in a volume ratio of 1 / 1, and the appearance of cracks on the sample surface was observed and recorded as the appearance of cracks. The time when the cracks began to appear was calculated. To reduce experimental errors, each sample was measured 5 times, and the average value was recorded and calculated as the final result;

[0162] 2. Test results

[0163] The test results of various embodiments and comparative examples are shown in Table 4.

[0164] Table 4 Test results of embodiments and comparative examples

[0165]

[0166]

[0167] It can be seen from Table 6 that the polymer composition prepared by the present invention has good chemical solvent resistance and water resistance, and also has good mechanical properties; specifically: the notched impact is not less than 18 kJ / m 2 , the contact angle is not less than 85°, and the cracking time is not less than 360s.

[0168] It can be seen from Comparative Example 3 that if vinyl siloxane is not added during the synthesis of the fluorine-silicon-containing multi-layer core-shell structure polymer, the hydrophobicity and chemical resistance of the polymer composition obtained subsequently are poor.

[0169] It can be seen from Comparative Example 4 that if the amount of fluorinated silicone is too much, the impact of the subsequently obtained polymer composition will be significantly reduced. This may be because when the amount of fluorinated silicone is too much, the polybutadiene content in the fluorinated silicone multilayer core-shell structure polymer will decrease, and thus the impact performance of the ABS resin will decrease.

[0170] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A multilayer core-shell structure polymer containing fluorine and silicon, comprising a core layer, an intermediate layer and an outer shell layer, characterized in that: Based on 100 parts by dry weight of the inner core and the middle layer, the outer shell layer comprises the following components: 5-25 parts of fluorinated silicone; 5-15 parts of vinyl siloxane; Alkyl siloxane 0-20 parts, The number of the intermediate layers is n, where n is a positive integer of 0 to 10; and the core includes a diene polymer.

2. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 1, characterized in that: The fluorine-containing siloxane includes one or more of trifluoropropylmethylcyclotrisiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane or 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane.

3. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 1, characterized in that: The vinyl siloxane includes one or more of tetramethyltetravinylcyclotetrasiloxane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane or vinyltriisopropoxysilane.

4. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 1, characterized in that: The alkylsiloxane includes one or more of octamethylcyclotetrasiloxane, hexamethyldisiloxane, hexaethyldisiloxane, methyltriethoxysilane or 1,3-octyltetramethyldisiloxane.

5. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 1, characterized in that: The average particle size of the core is 290 to 330 nm; preferably, the core comprises polyconjugated diene and / or polyconjugated diene-coated inorganic particles; further, the inorganic particles are one or more of silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, titanium dioxide or rare earth oxides.

6. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 1, characterized in that: The intermediate layer is obtained by emulsion polymerization of components including the following compounds: A11: 40 to 79.9 wt % of at least one vinyl aromatic olefin, based on the intermediate layer; A12: 10 to 39.9 wt % of acrylonitrile monomer based on the middle layer; A13: 10 to 29.9 wt % of a divinyl compound, based on the intermediate layer; The mass ratio of the middle layer to the inner core is 20:80 to 80:20 on a dry basis.

7. The fluorine-silicon-containing multilayer core-shell structure polymer according to claim 6, characterized in that: The divinyl compound structural formula is as follows: wherein R1 is selected from substituted or unsubstituted alkylene, cycloalkylene, alkylene ester, cycloalkylene ester, alkyleneoxy, cycloalkyleneoxy, arylene, arylalkylene, and heteroarylene; and the number of carbon atoms in R1 is 1 to 20; R2 and R3 are independently selected from hydrogen, alkyl, cycloalkyl, alkylcarboxyl, cycloalkylcarboxyl, alkoxy, cycloalkyloxy, aryl, aralkyl, and heteroaryl groups having 1 to 20 carbon atoms.

8. A method for preparing the fluorine-silicon-containing multilayer core-shell structure polymer according to any one of claims 1 to 7, characterized in that: The steps include: S1. Prepare or prepare the kernel; S2. Preparation of core-shell emulsion: A11, A12 and A13 were emulsion polymerized in the presence of the core; S3. polymerizing the product obtained in step S2, fluorinated siloxane, alkyl siloxane and vinyl siloxane to obtain a polymer emulsion, and condensing the polymer emulsion at high temperature to obtain a fluorinated silicon-containing multilayer core-shell structure polymer.

9. The preparation method according to claim 8, characterized in that: The polymerization reaction temperature is 60-90°C, the polymerization reaction time is 2-6h; the high temperature condensation temperature is 80-100°C.

10. A polymer composition, characterized in that The composition comprises the following components calculated by weight: 15-40 parts of the fluorine-containing silicon-containing multilayer core-shell structure polymer according to any one of claims 1 to 7 or the fluorine-containing silicon-containing multilayer core-shell structure polymer prepared by the preparation method according to claim 8 or 9; 60-80 parts of styrene-acrylonitrile copolymer and / or styrene-acrylonitrile-acrylate copolymer.

11. The polymer composition according to claim 10, characterized in that: The invention also comprises 0.1 to 5 parts by weight of other components, wherein the other components include one or more of fillers, reinforcing agents, dyes, lubricants, mold release agents, stabilizers, antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides or foaming agents.

12. A method for preparing the polymer composition according to claim 10 or 11, characterized in that: The steps include: The components are mixed, extruded through a twin-screw extruder, cooled, and granulated to obtain a polymer composition.

13. Use of the polymer composition according to claim 12 in the preparation of materials for automobiles, household appliances and office equipment.

Citation Information

Cited By

  • Preparation method of polyacrylate foaming regulator

    CN119875034A

  • Multilayer core-shell structure polymer containing fluorine and silicon, preparation method for resin composition comprising same, and use thereof

    WO2026098327A1